The Captive Imagination: Inhumanity, Animality, and Matthew Barney’s Cremaster 2 - Sharma, Devika (Humanimalia, 2015)
Taking an outset in American artist Matthew Barney’s film Cremaster 2 (1999), which is a part of the expansive work The Cremaster Cycle, this essay asks how notions of captivity reflect upon our concepts of inhumanity and animality. Captivity and confinement are in themselves favored themes of the popular imagination, but Barney’s speculative film suggests that notions of captivity also form part of the framework through which we imagine aspects of inhumanity and animality. Discussing the film in the light of contemporary theoretical reflections on what is commonly termed “the question of the inhuman” and “the question of the animal,” respectively, I understand the film to be a visual engagement with captivity and its significance for the discourses, images, and institutions that govern the boundaries of the human.